Safety and bioavailability of silver hydrosol as a source of silver added for nutritional purposes to food supplements. (28th March 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion on the safety and bioavailability of silver hydrosol as a source of silver added for nutritional purposes to food supplements. Silver hydrosol is a suspension comprised of a mixture of positively charged silver ions and silver metal particles in water. The study report submitted, being a gastric disappearance study performed in six individuals, did not provide information on the systemic absorption of silver as such, and was not able to provide information on the bioavailability of silver from silver hydrosol. If silver from silver hydrosol is systematically available a complete toxicological evaluation is needed for its assessment. The application dossier was limited to an acute toxicity study with silver hydrosol and references to toxicological studies performed with forms of silver (e.g. salts of silver) which were considered neither relevant nor adequate to the risk assessment of silver hydrosol. The Panel concluded that the submitted data are insufficient to characterise the silver hydrosol regarding its nano specific properties and to assess either the bioavailability of silver from the source or the safety of the silver hydrosol as a source of silver added for nutritional purposes to food supplements.